Epistatic Analysis of the Contribution of Rabs and Kifs to CATCHR Family Dependent Golgi Organization - Liu, Shijie; Majeed, Waqar; Grigaitis, Pranas; Betts, Matthew J.; Climer, Leslie K.; Starkuviene, Vytaute; Storrie, Brian (Frontiers in Cell and Developmental Biology, 2019)
Multisubunit members of the CATCHR family: COG and NRZ complexes, mediate, respectively, intra-Golgi and Golgi to ER vesicle tethering. We systematically addressed the genetic and functional interrelationships between Rabs, Kifs, and retrograde CATCHR family proteins, namely, COG3 and ZW10, that are necessary to maintain the organization of the Golgi complex. We scored the ability of siRNAs targeting 19 Golgi-associated Rab proteins and all 44 human Kifs, microtubule-dependent motor protein, to suppress CATCHR-dependent Golgi fragmentation in an epistatic fluorescent microscopy-based assay. We found that co-depletion of Rab6A, Rab6A’, Rab27A, Rab39A and two minus- end Kifs, namely KIFC3 and KIF25, suppressed both COG- and ZW10-dependent Golgi fragmentation. ZW10-dependent Golgi fragmentation was suppressed selectively by a separate set of Rabs: Rab11A, Rab33B and the little characterized Rab29. 10 Kifs were identified as hits in ZW10-dependent Golgi fragmentation, and, in contrast, to the double suppressive Kifs, were predominantly plus-end motors. No Rabs or Kifs selectively suppressed COG3-dependent Golgi fragmentation suggesting a hierarchical relationship in which the COG complex functions upstream of the ZW10 complex. Protein-protein interaction network analysis indicated putative direct and indirect links between suppressive Rabs and tether function. Validation of the suppressive hits by EM confirmed a restored organization of the Golgi cisternal stack. Based on these outcomes, we propose a three-way competitive model of Golgi organization in which Rabs, Kifs, and tethers modulate sequentially the balance between Golgi-derived vesicle formation, consumption, and off-Golgi transport.